Mills-Symon Oral History Transcript - Symon, Keith; Mills, Fred (My University, 2009)
Transcript of an oral history with Fred Mills, ex director of the Physical Sciences Laboratory , and Keith Symon, ex director of the Synchrotron Radiation Center. Conducted by Eric Verbeten.
Keywords: Synchrotron, Mills, Symon